Recidivism Patterns Among Two Types of Juvenile Homicide Offenders: A 30-Year Follow-Up Study - Khachatryan, Norair (International journal of offender therapy and comparative criminology, 2018)
Although juvenile homicide has been a matter of concern in the United States since the 1980s, prior research has not addressed long-term recidivism patterns for convicted juvenile murderers. Furthermore, a prominent juvenile homicide typology had not previously been tested with U.S. offenders. The present study examined whether juvenile offenders who killed or attempted to kill during the commission of a crime differed from those who killed due to some type of conflict on pre-incarceration, incarceration, and post-incarceration variables. These offenders were sentenced to adult prison in the early 1980s. Follow-up data spanned 30 years. The results indicated that approximately 88% of released offenders have been rearrested. Analyses of pre-incarceration variables revealed that crime-oriented offenders were significantly more likely to commit the homicide offense using accomplices than conflict-oriented offenders, and the latter were significantly more likely to use a firearm during the homicide incident. The circumstances of the homicide, however, were not significantly related to any other pre-incarceration variables, release from prison, number of post-release arrests, and number of post-release violent offenses. The implications of the findings, their comparability to previous follow-up research on this typology, and avenues for future research are discussed.